1989
DOI: 10.1002/tera.1420390404
|View full text |Cite
|
Sign up to set email alerts
|

Congenital defect rates among spontaneous abortuses: Twenty years of monitoring

Abstract: A 20-year study of 1,124 spontaneously aborted embryos and fetuses found 214 (19.0%) to have a localized defect or identifiable syndrome. No clear trend of change over time was noted. The rate is compared with other studies of spontaneously aborted specimens and is approximately ten times higher than in newborns. Forty (3.6%) had neural tube defects and 30 (2.7%) had a clinically recognized chromosomal phenotype. Fifteen had Turner's phenotype, four trisomy 18, and 11 triploidy. Amniotic bands occurred in eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 16 publications
0
18
1
3
Order By: Relevance
“…The trisomy D [12][13][14][15] chromosomal anomaly exhibits variable Placental maturation, reduced villous vasculature and giant cytophoblast in 50% or more of villi [Table/ Fig-4]. Tetrasomy 12 is a well-recognised chromosomal error with usually lethal anomalies, severely malformed fetus with normal birth weight and essentially normal placenta [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trisomy D [12][13][14][15] chromosomal anomaly exhibits variable Placental maturation, reduced villous vasculature and giant cytophoblast in 50% or more of villi [Table/ Fig-4]. Tetrasomy 12 is a well-recognised chromosomal error with usually lethal anomalies, severely malformed fetus with normal birth weight and essentially normal placenta [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tetrasomy 12 is a well-recognised chromosomal error with usually lethal anomalies, severely malformed fetus with normal birth weight and essentially normal placenta [13]. Shepard et al, [14] undertook 20 y analysis of aborted specimen and found that 19% of fetus had a localized defect. Neural tube defects existed in 3.6% cases and recognizable abnormal phenotypes due to chromosomal errors were present in 2.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most common anomalies are defects in positioning of the cardiac outflow tract and in closing of the ventricular septum, palate or neural tube; these occur at frequencies of ~0.2%, ~0.4%, ~0.1% and ~0.1% of live births, respectively (Genisca et al, 2009;Hoffman and Kaplan, 2002). Although these defects are found most commonly in isolation, they are also observed as components of a large number of syndromes that feature multiple congenital anomalies, and they are more common in embryos that have undergone spontaneous abortion (Shepard et al, 1989). In both humans and mice, the genetic contributions to these processes are complex (Copp and Greene, 2010;Jugessur and Murray, 2005;Juriloff and Harris, 2008;Kibar et al, 2007a;Moon, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If a miscarriage occurs for maternal reasons, they are as follows: in addition to uterine malformation and cervical insufficiency, amongst others, hormone deficiency, thrombophilia, immunologic factors, myoma and extragenital causes may play a role [6] . The fetal causes of miscarriage most commonly include chromosome aberrations, which are responsible for nearly half of all miscarriages [4,[7][8][9][10][11] ; in this group, 95% of all of these cases happen to be numerical chromosome aberrations. The paternal causes of miscarriages are usually associated with the possible ab-erration of sperm cells [4] .…”
Section: Introductionmentioning
confidence: 99%